2022
DOI: 10.4103/jpbs.jpbs_674_21
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Knowledge, and Acceptance of Dental Implants among the Geriatric Population of Jeddah, Saudi Arabia

Abstract: Background: Dental implants (DI) are gaining popularity among the general population, and special consideration has been given to the geriatric population in the replacement of missing teeth subject to their medical stability. The study aimed to assess the awareness, knowledge, and acceptance regarding DI among the geriatric population of Jeddah, Saudi Arabia. Methodology: A cross-sectional survey was carried out through face-to-face interviews using a pretested and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…Whereas the knowledge related to dental implants could have been more satisfactory, only 4.5% showed good knowledge. The willingness to replace the current prosthesis with a dental implant was found in 49.6%, and it was also observed that 40% of the participants were using some tooth-supported xed dental prosthesis [23].…”
Section: Discussionmentioning
confidence: 96%
“…Whereas the knowledge related to dental implants could have been more satisfactory, only 4.5% showed good knowledge. The willingness to replace the current prosthesis with a dental implant was found in 49.6%, and it was also observed that 40% of the participants were using some tooth-supported xed dental prosthesis [23].…”
Section: Discussionmentioning
confidence: 96%
“…A previous study by Alqahtani et al showed that the source of information regarding dental implants among the participants was mainly self-education (46%) [ 1 ]. However, our study shows that 44% of participants reported that their main source of information about dental implants was their dentist.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth loss is a critical oral health problem that negatively affects the population worldwide [ 1 , 2 ]. The prevalence of tooth loss among the adult Saudi population is reported to be high [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A convenience sampling approach was employed. The required sample size was estimated at a minimum of 380 participants, calculated with a 5% margin of error, a 95% confidence level, a dentist population of 27,181 [ 13 ], and a presumptive response distribution of 50%. This calculation was determined using the Raosoft online sample size calculator.…”
Section: Methodsmentioning
confidence: 99%